PERAN KEWIRAUSAHAAN MAHASISWA TERHADAP UMKM BERBASIS DIGITAL - Suryani Sihombing; Dino Simbolon; Pransisko Purba; Dames Simbolon; Patricia Herpayanti; Nalom Siagian (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
In facing business competition in the digital economy era, the digitalization of Micro, Small, and Medium Enterprises (MSMEs) has become a primary necessity. By participating in technology-based entrepreneurial activities, students have significant opportunities to act as agents of change. This study aims to explore how student entrepreneurship contributes to the development of digital-based MSMEs. The research was conducted using a qualitative approach, including observation, interviews, and literature review. The findings indicate that student entrepreneurship supports product innovation, digital marketing, the use of social media and marketplaces, and the improvement of MSME actors’ digital literacy. Consequently, these contributions enhance competitiveness and expand market reach for MSMEs. However, challenges remain, such as limited resources and the readiness of MSME actors to adopt digital